2016
DOI: 10.14419/ijasp.v4i1.5914
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of estimates using censored samples from Gompertz model: Bayesian, E-Bayesian, hierarchical Bayesian and empirical Bayesian schemes

Abstract: <p>This paper aims to introduce a comparative study for the E-Bayesian criteria with three various Bayesian approaches; Bayesian, hierarchical Bayesian and empirical Bayesian. This study is concerned to estimate the shape parameter and the hazard function of the Gompertz distribution based on type-II censoring. All estimators are obtained under symmetric loss function [squared error loss (SELF))] and three different asymmetric loss functions [quadratic loss function (QLF), entropy loss function (ELF) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
(83 reference statements)
0
3
0
Order By: Relevance
“…Han [11] introduced the expected Bayesian (E-Bayesian) estimation method which is very simple and it's a special Bayesian method used in the area related for the life testing of products with high reliability, small sample size or censored data. Many researchers applied the E-Bayesian method to many distributions, such as, Okasha [12], Azimi et al [13], Okasha [14], Reyad and Ahmed [15], Reyad and Ahmed [16], Nasiri and Esfandyarifar [17], Reyad et al [18], EL-Sagheer [19], Shawky and Al-Aboud [20], Reyad et al [21], Reyad and Othman [22], Han [23], Okasha [24], Rabie and Li [25], Algarni et al [26], Han [27], Piriaei et al [28] and Rabie and Li [29].…”
Section: Introductionmentioning
confidence: 99%
“…Han [11] introduced the expected Bayesian (E-Bayesian) estimation method which is very simple and it's a special Bayesian method used in the area related for the life testing of products with high reliability, small sample size or censored data. Many researchers applied the E-Bayesian method to many distributions, such as, Okasha [12], Azimi et al [13], Okasha [14], Reyad and Ahmed [15], Reyad and Ahmed [16], Nasiri and Esfandyarifar [17], Reyad et al [18], EL-Sagheer [19], Shawky and Al-Aboud [20], Reyad et al [21], Reyad and Othman [22], Han [23], Okasha [24], Rabie and Li [25], Algarni et al [26], Han [27], Piriaei et al [28] and Rabie and Li [29].…”
Section: Introductionmentioning
confidence: 99%
“…Prakash (2016) discussed about the Bayes prediction bound length under different censoring plans and statistical inference based on a random scheme under progressive Type-II censored data for Gompertz model. Reyad et al (2016) introduced a comparative study for the E-Bayesian criteria with three various Bayesian approaches; Bayesian, hierarchical Bayesian and empirical Bayesian.…”
Section: Introductionmentioning
confidence: 99%
“…Reyad and Othman [24] constructed the Bayes and E-Bayes approaches for estimating the unknown shape parameter of the Kumaraswamy distribution based on type-ii censored data and by considering squared error, LINEX, Degroot, quadratic. Reyad et al [25] obtained the Bayes, E-bayes, hierarchical Bayes and empirical Bayes estimates of the unknown shape parameter and hazard function of the Gompertz distribution based on type-II censoring and by considering squared error loss, quadratic loss entropy loss and LINEX functions. The main object of this study is to suggested a new modification for the E-Bayes method of estimation to yield a new technique namely quasi-E-Bayes method (or briefly QE-Bayes).…”
Section: Introductionmentioning
confidence: 99%